Type II oestrogen binding sites in human colorectal carcinoma. - Piantelli, M (1990)
Seven cases of colorectal adenocarcinomas were investigated for the presence of oestrogen receptors and progesterone receptors. The tumours specifically bound oestradiol. This binding almost exclusively resulted from the presence of high numbers of type II oestrogen binding sites. Oestrogen receptors were absent or present at very low concentrations. Immunohistochemical investigation of nuclear oestrogen receptors gave negative results. This indicates that antioestrogen receptor antibodies recognise oestrogen receptors but not type II oestrogen binding sites. The presence of specific type II oestrogen binding sites and progesterone binding offers further evidence for a potential role for these steroids and their receptors in colorectal carcinoma.